The protected species Pseudophilotes bavius hungarica (Diószeghy, 1913): oviposition strategy, new records and conservation (Lepidoptera: Lycaenidae) - Andrei Crisan; Tibor-Csaba Vizauer; László Rákosy (SHILAP)
Pseudophilotes bavius hungarica (Diószeghy, 1913) is a Transylvanian endemic of conservation interest. We made observations regarding its oviposition strategy, and established its preference for floral stems of Salvia nutans L. taller than five centimeters. Salvia transsilvanica Schur was also confirmed as a host plant for P. bavius hungarica. The distribution map of this subspecies was completed in two localities from the south of the Transylvanian Plain, Râpa Lechint¸a and Râpa Da˘ta˘ reni. We reported presence of P. bavius in Tulcea County for the first time, thus supporting the hypothesis that it colonised Dobrogea via Ukraine alongside P. bavius bavius (Eversmann, 1832) and it did not spread from Turkey and Bulgaria alongside P. bavius egea. Many conservation threats that may lead to population fragmentation and extinction have been identified.